PAGERDUTY: REVOLUTIONIZING INCIDENT MANAGEMENT THROUGH AUTOMATION - Jugnu Misal (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores PagerDuty's transformative role in modernizing incident management through automation. The article examines how PagerDuty's platform addresses the growing challenges of complex IT infrastructures, cloud-native architectures, and distributed systems. Through intelligent, alert management, automated escalation workflows, and extensive integration capabilities, PagerDuty revolutionizes how organizations handle incidents. The article details the platform's technical implementation, best practices for deployment, and methods for measuring success. The article demonstrates significant improvements in operational efficiency, team productivity, and service quality while highlighting substantial cost savings and strategic benefits for organizations implementing automated incident management solutions.